2011
DOI: 10.1007/s13197-011-0441-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frozen storage on the characteristics of a developed and commercial fish sausages

Abstract: The effect of frozen storage on the physiochemical, chemical and microbial characteristics of two types of fish sausages was studied. Fish sausages developed (DFS) with a spice-sugar formulation and commercial fish sausages (CFS) were stored at -20 °C for 3 months. Fresh DFS contained 12.22% lipids and had a 3.53 cfu/g total bacteria count (TBC) whereas, CFS contained 5.5% lipids and had a 4.81 cfu/g TBC. During storage, TBC decreased significantly (p < 0.05) in DFS whereas it did not change (p > 0.05) in CFS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…Protein content was 13.9±0.2%, lowerthanin sausages made by pink salmon (22.4%) (Oliveira et al, 2013), crimson snapper (19.7%) (Al-Bulushi et al, 2013), rohu (18%) (Sini et al 2008), African Catfish and Nile puffer (18.1 and 19.6% respectively) (Ahmed and Elhaj 2011) and in fermented saithe and salmon sausages (18.0-21.0%) (Nordvi et al, 2007). A high lipid content (29.6±1.0%) was detected in the product: although our samples did not contain animal fat sources as described in previous studies (Dincer and Cakli, 2010), the values observed were strongly higher than what found in fish-sausages without landbased animal fat additions (between 5 and 7%) (Nordvi et al, 2007;Sini et al, 2008;Olivera Filho et al, 2012;Al-Bulushi et al, 2013), probably due to the fatty level of the raw material used for the production of the frankfurters (trimmings comprehensive of the belly flaps). Ash content was attested at 2.6%, according with Oliveira et al (2013) who found a content of 2.7% in hot smoked pink salmon sausages.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Protein content was 13.9±0.2%, lowerthanin sausages made by pink salmon (22.4%) (Oliveira et al, 2013), crimson snapper (19.7%) (Al-Bulushi et al, 2013), rohu (18%) (Sini et al 2008), African Catfish and Nile puffer (18.1 and 19.6% respectively) (Ahmed and Elhaj 2011) and in fermented saithe and salmon sausages (18.0-21.0%) (Nordvi et al, 2007). A high lipid content (29.6±1.0%) was detected in the product: although our samples did not contain animal fat sources as described in previous studies (Dincer and Cakli, 2010), the values observed were strongly higher than what found in fish-sausages without landbased animal fat additions (between 5 and 7%) (Nordvi et al, 2007;Sini et al, 2008;Olivera Filho et al, 2012;Al-Bulushi et al, 2013), probably due to the fatty level of the raw material used for the production of the frankfurters (trimmings comprehensive of the belly flaps). Ash content was attested at 2.6%, according with Oliveira et al (2013) who found a content of 2.7% in hot smoked pink salmon sausages.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Fish and fishery products are susceptible to chemical and physical changes during frozen storage. These changes adversely affect product's quality and storage stability (Al-Bulushi et al, 2013). Serious lipid oxidation in fish protein isolate is caused by hemoglobin and myoglobin during pH-shift process and final product storage (Rechards and Hultin, 2002;Nolsøe and Undeland, 2009).…”
Section: Fish Burger Prototypesmentioning
confidence: 99%
“…Several techniques are used for preserving fishery formulated products. Among these methods using spices and herbs, which are natural antioxiants and antibacterial, and covring the produt with batter/and breading are common techniques in the seafood industry (Al-Bulushi et al, 2013;Shaviklo et al, 2010;. Battering and breading of fish burger can act as oxygen barrier, which provide better protection against lipid oxidation and microbial deterioration (Joseph et al, 1992;Vanitha et al, 2013).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…This bacterium does not exist originally in the fish, being introduced during handling or by contact with contaminated water and its presence is a major problem for public health because of its pathogenic character (Al-Bulushi et al 2011). According to Spricigo et al (2008) the presence of Salmonella in food indicates inadequacy of the product for consumption and the bacteria of this genus are primarily responsible for foodborne outbreak.…”
Section: Microbiological Characterizationmentioning
confidence: 99%